Ethnomedicinal Studies, Chemical Composition, and Antibacterial Activity of the Mammea americana L. Bark in the Municipality of Cértegui, Chocó, Colombia - Lina Mosquera-Chaverra; Manuel Salas-Moreno; José Marrugo-Negrete (Hindawi Limited, 2022)
Mammea americana L. is a plant with diverse medicinal uses in the municipality of Cértegui, Chocó, Colombia. This research characterized the ethnomedicinal, chemical, and antibacterial activities of the bark of Mammea americana. Through interviews and semistructured surveys with the community, its ethnomedicinal uses were determined. Compounds present in the bark extract were identified and quantified by gas chromatography-coupled to mass spectrometry (GC-MS), and a qualitative analysis was performed by preliminary phytochemistry. Antibacterial activity and minimum inhibitory concentration (MIC) were carried out by agar diffusion and dilution methods, respectively, using ethanolic and aqueous extracts. Ethnomedical data showed that the bark is used to treat 14 conditions, the most representative being gallstones, prostate inflammation, and malaria. Preliminary phytochemical analyses showed the existence of several secondary metabolites such as tannins, alkaloids, flavonoids, triterpenes and/or steroids, quinones, and saponins. A total of 29 compounds were identified; the most abundant were ethyl 5-oxo-4-(p-toluidine)-2,5-dihydro-3-furancarboxylate, phenol, 4,4',4"-ethylidynetris, nerolidol, 19-hydroxy-13-epimanoyl oxide, α-elemene, and δ-cadinene. The results showed remarkable antibacterial activity of the ethanolic extract (20 mg/ml) against Staphylococcus aureus (22.6 mm) and Escherichia coli (19.6 mm) and of the crude water extract (20 mg/ml) against Staphylococcus aureus (18.5 mm) and Escherichia coli (12.4 mm). The strongest MIC was for the ethanolic extract with values of 0.357 and 0.897 mg/ml against S. aureus and E. coli strains, respectively, while in the aqueous extract, S. aureus (3.99 mg/ml) and E. coli (4.3 mg/ml) were recorded. It is assumed that the compounds identified in this study could be responsible for the antibacterial activity of the species, as well as the relationship of the identified compounds and metabolites with the ethnomedical uses given by the community, providing a scientific and traditional basis for its different traditional medical uses.